Implementing Religious Moderation in Social Interactions of Tobelo Society: A Qualitative Analysis - Nurhayati Masani; Icksan Asry Fabanjo (International Islamic Studies Development and Research Center (IISDRC), 2026)
Religious moderation is a balanced, non-extreme approach to religion that respects differences. This concept encourages religious adherents to have a deep understanding of their own faith while respecting the beliefs of others. In practice, religious moderation means following religious teachings without imposing them on others, avoiding extremist or radical attitudes, and fostering harmony among fellow citizens. This study aims to analyze how religious moderation is implemented in Tobelo. The study employs a qualitative research method using a group case study approach, which describes the mechanisms of a process or relationship and provides a comprehensive overview in both verbal and numerical forms. Data collection techniques in this study include observation and interviews. The results of the study indicate that the people of Tobelo view moderation as a middle path that allows them to remain steadfast in their own beliefs while maintaining harmonious relationships with adherents of other religions. The implementation of religious moderation in Tobelo is evident in various aspects of daily life. In a social context, the people of Tobelo actively engage in interfaith interactions through community service activities, traditional ceremonies, and celebrations of major religious holidays that are often attended by people of different faiths.